The Lifetime of Email Messages: A Large-Scale Analysis of Email Revisitation - Alrashed, Tarfah; Awadallah, Ahmed; Dumais, Susan (In Proceedings of the 2018 ACM SIGIR Conference on Human Information Interaction and Retrieval (CHIIR), 2018)
Email continues to be one of the most important means of online communication, leading to a number of challenges related to information overload and email management. To better understand email management practices in detail, we examine the distribution of visits to emails over time. During their lifetime, emails may be visited one or more times, and with each visit different actions may be taken. Emails that are revisited over time are especially interesting because they represent an opportunity to improve email management and search. In this paper, we present a large-scale log analysis of email revisitation, the activities that people perform on revisited email messages (e.g. responding to, organizing or deleting messages, and opening attachments), and the strategies they use to go back to these emails. We find that most emails have a short lifetime, with more than 33% having a lifetime of less than 5 minutes. We also find that deleting is the most common action taken on messages visited once, and that responding and organizing are more common for messages visited more than once. We complement the log analysis with a survey to understand the motivation behind revisits and the types of emails that are revisited. The survey results show that 73% of the visits are to find information (e.g. a link or document, instructions to perform a task, or answers to questions), while 20% of revisits are to respond to the email. Our findings have implications for designing email clients and intelligent agents that support both short- and long-term revisitation patterns.